Self-management as Support to an Advanced Traveler Information System - Pasin, Marcia; Perini, Felipe Silvano; Bazzan, Ana L. C. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2012)
Advanced traveler information systems (ATIS) are growing in popularity posing new challenges to distributed infrastructures. Services and data tend to be distributed, heterogeneous, and there are issues related to elastic and increasing demand, failures and load peaks. Management of such infrastructures is a complex task. To address these issues, a promising approach is to implement system management as an autonomic service. In this paper we propose a self-managed system (SMS) to support a distributed infrastructure running an ATIS. Based on current and previous status, the SMS adapts itself to achieve efficient service and high availability. Experimental evaluation showed that the ]system is efficiently reactive due to changing demand and occurrence of faults.